Reframing Mandatory and Additional Mahr: A Maqasid Asy-Shari’ah and Socio-Legal Analysis of Indonesian Muslim Marriage Practices - Muhammad Nabat Ardli; Reza Hilmy Luayyin (Journal of Islamic Civilization, 2025)
The mahr is an essential element of Islamic marriage, normatively established by the Qur’an and Hadith as a wife’s right and as a symbol of women’s dignity. However, in practice, Muslim communities, including those in Indonesia, often incorporate additional elements such as seserahan (gifts) and bawaan (additional mahr), which are more rooted in local custom and socio-cultural construction. This study aims to critically examine the legal and social positions of both the obligatory mahr and these additional forms through the perspectives of Maqāṣid al-Sharīʿah and the sociology of Islamic law. Using a qualitative approach based on interviews, participant observation, and documentation in Probolinggo society, this research employs contextual hermeneutics to interpret normative texts alongside lived practices. The findings show that seserahan and bawaan have undergone a functional shift: from voluntary cultural expressions into socially expected obligations that often serve as markers of status and symbolic capital. While mahr consistently reflects the maqāṣid principles of protection of honor (hifz al-ard), lineage (hifz an-nasl), and wealth (hifz al-mal), seserahan increasingly operates within a socio-economic logic that may contradict the principle of taysīr (ease), particularly when it creates structural financial pressure on the groom’s family. This study contributes by proposing a maqāṣid-based socio-legal framework that distinguishes between ʿurf as a source of social cohesion and ʿurf as a mechanism of latent coercion. It demonstrates that the transformation of cultural practices into quasi-obligatory norms represents a form of “normative expansion” beyond classical Islamic legal requirements. From a sociological perspective, these practices illustrate the dynamic negotiation between Islamic legal norms and local culture, where law is reproduced through symbols, social expectations, and power relations. The article concludes by advocating for a reinterpretation of marriage practices through premarital education and the promotion of a “dignified yet simple marriage” model that restores the ethical.